Rhabdomyosarcoma in the urinary bladder of an American Pitbull Terrier (Research, Society and Development, 2021)
Botryoid rhabdomyosarcoma is a variant of embryonic rhabdomyosarcoma and originates in striated muscle cells, or precursors of these cells, so they can start in parts of the body with the absence of striated muscle, such as the urogenital tract. Ser, the dogs affected are young up to two years old and the neoplastic masses look like a bunch of grapes. The objective of the present report was described as a case of botryoid rhabdomyosarcoma in a 16-month-old American Pittbull Terrier dog that presented a mass inside the urinary bladder, later diagnosed through histopathological and immunohistochemical examination. The mass was multilobulated, firm, pinkish to red with multifocal areas of necrosis and was adhered to the mucosa of the most cranial region of the urinary vesicle, emitting disseminated branches towards the bladder triangle. Microscopically, a neoplasm is discovered by two cell populations interspersed with a myxoid matrix, one composed of small, round cells, with scarce cytoplasm and hypercolored basophilic nucleus and the other by elongated cells, with eosinophilic and paracentral cytoplasm, both as having moderate and pleomorphism 2 mitosis figures per field (400 x). Increased cell density was observed below the bladder epithelium. A combination of complementary tests was conclusive for the diagnosis of neoplasia.